2012
DOI: 10.1021/jf301848s
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Volatile Aroma Components, Flavanones, and Polymethoxylated Flavones in Shiikuwasha (Citrus depressa Hayata) Peels of Different Cultivation Lines

Abstract: Citrus peels are important sources of various pleasant aroma compounds and valuable bioactive substances. To investigate differences in the composition and content of Shiikuwasha (Citrus depressa Hayata) peels from different cultivation lines, the composition of volatile aroma components, flavanones, and polymethoxylated flavones (PMFs) in four Shiikuwasha cultivation lines was examined. The composition of volatile aroma components in cold-pressed extracts of Shiikuwasha peels was analyzed using gas chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 38 publications
1
36
1
Order By: Relevance
“…These trends might also be related to the flavonoid composition of the fruit peels. A previous study has reported that ‘Izumi kugani’ peel contains a larger amount of total flavonoid content and distinctive flavanone composition owing to the presence of neohesperidin compound, whereas peels of other Shiikuwasha cultivation lines had high hesperidin contents . Neohesperidin reportedly has greater radical‐scavenging abilities compared with those of hesperidin …”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…These trends might also be related to the flavonoid composition of the fruit peels. A previous study has reported that ‘Izumi kugani’ peel contains a larger amount of total flavonoid content and distinctive flavanone composition owing to the presence of neohesperidin compound, whereas peels of other Shiikuwasha cultivation lines had high hesperidin contents . Neohesperidin reportedly has greater radical‐scavenging abilities compared with those of hesperidin …”
Section: Resultsmentioning
confidence: 95%
“…‘Izumi kugani’ juice was relatively more astringent and acidic bitter, whereas ‘Kaachi’ juice had the opposite taste values. Flavonoid content and composition in the fruits might have affected the occurrence of these aftertastes; whereas a previous study has reported that the peel part of ‘Izumi kugani’ fruit has a flavonoid content greater than that in three other cultivation lines . Moreover, it had a distinctive amount of neohesperidin, whereas other Shiikuwasha cultivation lines contained its flavanone glycoside isomer, hesperidin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations